Pengaruh Beban Kerja, Job Insecurity, Dan Salary Satisfaction Terhadap Turnover Intention (Studi Kasus Pada Karyawan PT. Mentari Agung Jaya Usaha) - Zahrara, Safitri Ariana; Hendrawan, Koen (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The phenomenon of high employee turnover intention has been widely discussed in previous studies due to its impact on human resource stability and company performance. Workload, job insecurity, and salary satisfaction are among the variables considered to influence turnover intention. This study aims to examine the effect of Workload (X1), Job Insecurity (X2), and Salary Satisfaction (X3) on Turnover Intention (Y) among operational and administrative employees of PT. Mentari Agung Jaya Usaha. The research method used a quantitative approach with a sample of 57 employees, determined through non-probability sampling using a purposive sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS version 4.1.1.5. The results show that workload and job insecurity have a positive and significant effect on turnover intention, while salary satisfaction has no significant effect. Workload is the most dominant variable influencing turnover intention. The findings of this study are expected to serve as a consideration for companies in managing human resources.